Assessment of spine mobility in patients with ankylosing spondylitis by ultrasound scanning (preliminary data) - M. K. Kurbanmagomedov; K. V. Sakharova; A. B. Demina; Sh. F. Erdes (Современная ревматология, 2021)
Spine involvement in ankylosing spondylitis (AS) resulting in limited mobility requires a search for accurate, quantitatively methods of assessment of the decline of its function and monitoring of its dynamics. One of the promising methods for assessing movements in the spine in AS is ultrasound examination (US).Objective: to determine the relationship between the mobility of the spine measured sonographically, and the activity and functional status of patients with AS.Patients and methods. Spinal ultrasound was performed in 15 patients (10 men and 5 women, mean age 40.8±11.4 years, mean duration of the disease 5.5±3.5 years) with a confirmed diagnosis of AS, admitted to the V.A. Nasonova Research Institute of Rheumatology from April to August 2019. All patients underwent a double examination (at baseline and after 2 weeks) according to a specially developed protocol.Results and discussion. A comparative analysis of the results of sonographic measurements of the distance between the spinous processes of the vertebrae of the studied spine segment at baseline and after 2 weeks revealed a tendency towards an increase in these parameters both in the initial position and during flexion. There was no relationship between age, body mass index, duration of the disease and the distance between the spinous processes in all parts of the spine measured by sonography in initial position and during flexion. Correlation analysis data indicate the presence of a correlation between an increase in the distance between the spinous processes in the cervical and lumbar spine and a decrease in ESR, and i increase in the distance between the spinous processes in the lumbar spine and level of CRP. A weak negative relationship was found between the BASDAI index and the mobility of the spine at the LIV–V level and between sonographic measurements in all segment of the spine and the BASMI index.Conclusion. The sonographic method of determining the mobility of the spine can be recommended in patients with AS, both for initial examination and during follow-up, but it can't substitute the BASMI metrological index. Further research is needed to confirm the findings.